2008
DOI: 10.1037/0893-3200.22.1.153
|View full text |Cite
|
Sign up to set email alerts
|

How do constraints on leaving a marriage affect behavior within the marriage?

Abstract: Like relationship satisfaction, constraints on leaving a relationship have been described as a component of global commitment. But do constraints increase or decrease efforts to maintain the relationship? To address this question, the authors of the current article describe 3 independent studies of spouses and married couples. Across all studies, wives who perceived more constraints on leaving the marriage exhibited lower levels of negative behavior only when their husbands were relatively unconstrained. In St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

7
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…Second, some of the perceived constraint scales had low internal consistency, which may have limited statistical power to detect to differences among the groups on these scales. Third, some research has indicated that the ways in which constraints affect verbal aggression in relationships may depend in part on the other partner’s sense of constraints (Frye et al, 2008). Thus, future research on commitment and physical aggression could benefit from measuring both partners in a dyad.…”
Section: Discussionmentioning
confidence: 99%
“…Second, some of the perceived constraint scales had low internal consistency, which may have limited statistical power to detect to differences among the groups on these scales. Third, some research has indicated that the ways in which constraints affect verbal aggression in relationships may depend in part on the other partner’s sense of constraints (Frye et al, 2008). Thus, future research on commitment and physical aggression could benefit from measuring both partners in a dyad.…”
Section: Discussionmentioning
confidence: 99%
“…Although data from the sample described here are described in other articles (Baker & McNulty, 2010, in press; Fisher & McNulty, 2008; Frye, McNulty, & Karney, 2008; Little, McNulty, & Russell, 2010; Luchies, Finkel, McNulty, & Kumashiro, 2010; McNulty, 2008a, 2008b; McNulty & Fisher, 2008; McNulty & Hellmuth, 2008; McNulty & Russell, 2010; Russell & McNulty, 2011), there has been little overlap between the variables examined in these prior articles and the variables examined here. The two exceptions are that the five items that assessed participants’ tendencies to express forgiveness at baseline used in the present article were used in conjunction with five other items to that assessed participants tendencies to feel forgiveness to (a) predict changes in satisfaction and problems over 2 years in McNulty (2008a) and (b) predict changes in self-respect over 4.5 years in Luchies et al (2010).…”
mentioning
confidence: 96%
“…Although data from this sample are described in several articles (Baker & McNulty, 2010; Fisher & McNulty, 2008; Frye, McNulty, & Karney, 2008; Little, McNulty, & Russell, 2010; Luchies, Finkel, McNulty, & Kumashiro, 2010; McNulty, 2008a, 2008b; McNulty & Fisher, 2008; McNulty & Hellmuth, 2008; McNulty & Russell, 2010), there is little overlap between the variables examined in those studies and the variables examined here. The one exception is that McNulty and Russell described the same trajectories of marital satisfaction.…”
mentioning
confidence: 99%